MELANCHOLY AND INTELLECTUAL NETWORKS IN THE DIARY OF ALCIDES ARGUEDAS (1879-1946) - Diniz, Cláudio (Revista Gênero e Interdisciplinaridade, 2023)
The central objective of this article is to observe the construction of the melancholic idea in the work of the Bolivian historian Alcides Arguedas (1879-1946). The strategy used is the analysis of the author’s intellectual networks revealed in his personal diary. To this end, we sought to analyze the reception of the editions of the work Pueblo enfermo (1909), described in the Diary, through the author’s political and intellectual positioning in relation to Bolivian and world history.